Trashumancia, Espacio para Poesía y Arte : agosto 92 - Ocaranza, Jorge Octavio (dirección); Gutiérrez Ramírez, Alfredo (dirección) (Trashumancia, 1992)
Contiene obra de: José Javier Coz, Italo Calvino, Anna Coloma, Bernardo Ruiz, Leg Ortiz Monasterio, Severino Salazar, Nicanor Parra, Anne Sexton, Antonio López Mijares, Carla Gómez Bordes, Carlos Rosas, Ernesto Lumbreras, Guadalupe Angeles Huizard, Julia Astengo, Juan Gustavo Cobo Borda, Mauricio Ramírez, Mónica Nepote, Oscar Tagle, Raúl Ramírez y Víctor Manuel Pazarín.